Glycoside hydrolase family 32 is present in Bacillus subtilis phages. Issue 1 (December 2015) - Maaroufi, Halim; Levesque, Roger
Abstract Background Glycoside hydrolase family 32 (GH32) enzymes cleave the glycosidic bond between two monosaccharides or between a carbohydrate and an aglycone moiety. GH32 enzymes have been studied in prokaryotes and in eukaryotes but not in viruses. Findings This is the first analysis of GH32 enzymes inBacillus subtilis phage SP10, ϕNIT1 and SPG24. Phylogenetic analysis, molecular docking and secretability predictions suggest that phage GH32 enzymes function as levan (fructose homopolysaccharide) fructotransferase. Conclusions We showed that viruses also contain GH32 enzymes and that our analysesin silico strongly suggest that these enzymes function as levan fructotransferase.